2016
DOI: 10.1111/gcbb.12318
|View full text |Cite
|
Sign up to set email alerts
|

Comparing predicted yield and yield stability of willow and Miscanthus across Denmark

Abstract: To achieve the goals of energy security and climate change mitigation in Denmark and the EU, an expansion of national production of bioenergy crops is needed. Temporal and spatial variation of yields of willow and Miscanthus is not known for Denmark because of a limited number of field trial data. The semi-mechanistic crop model BioCro was used to simulate the production of both short-rotation coppice (SRC) willow and Miscanthus across Denmark. Predictions were made from high spatial resolution soil data and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Biomass yields are influenced by the amount and distribution of rainfall, which suggests that water availability is a key yield-building factor in this grass species (Gauder et al, 2012). High precipitation levels (Gauder et al, 2012) and soils capable of accumulating water (Arundale, Dohleman, Heaton, et al, 2014;Larsen, Jaiswal, Bentsen, Wang, & Long, 2016;Miguez, Maughan, Bollero, & Long, 2012;Wang et al, 2015) minimize variations in biomass yield. In this study, abundant precipitation in years 10 and 11 (2016 and 2017) contributed to an increase in the biomass yield of giant miscanthus (19.0-20.0 Mg DM ha −1 year −1 ).…”
Section: Czypionkamentioning
confidence: 99%
“…Biomass yields are influenced by the amount and distribution of rainfall, which suggests that water availability is a key yield-building factor in this grass species (Gauder et al, 2012). High precipitation levels (Gauder et al, 2012) and soils capable of accumulating water (Arundale, Dohleman, Heaton, et al, 2014;Larsen, Jaiswal, Bentsen, Wang, & Long, 2016;Miguez, Maughan, Bollero, & Long, 2012;Wang et al, 2015) minimize variations in biomass yield. In this study, abundant precipitation in years 10 and 11 (2016 and 2017) contributed to an increase in the biomass yield of giant miscanthus (19.0-20.0 Mg DM ha −1 year −1 ).…”
Section: Czypionkamentioning
confidence: 99%
“…There have been initiatives to develop a common process‐based model framework that can be applied to a range of different crops. For example, a common process‐based model approach has been developed using the BioCrop mechanistic modeling framework for willow (Wang et al ., ; Larsen et al ., ), switchgrass, and Miscanthus (Miguez et al ., , ), but as noted above, these models require large amounts of data input and this information was not collected as part of the Sun Grant Feedstock Regional Feedstock Partnership program.…”
Section: Introductionmentioning
confidence: 99%
“…For example, whilst it is suggested that globally, ecosystems dominated by ericoid and EMF can hold more soil C than those dominated by AMF (Averill et al, 2014) no research has considered whether EMF association in SRC Willow processes and sequesters assimilated carbon differently to AMF associating miscanthus. Utilizing established plantations of miscanthus and SRC willow, which exhibit contrasting photosynthetic pathways, growth rates and environmental tolerances (Larsen et al, 2016;Quinn et al, 2012;Bellarby et al, 2010), we applied 13 C -pulse labelling to investigate C assimilation and the transfer, distribution and persistence of plant derived C within microbial communities. 13 Cpulse labelling has previously been applied to agricultural systems (Tavi et al, 2013), grasslands (De Deyn et al, 2011;Leake et al, 2006;Ostle et al, 2000), peatlands (Biasi et al, 2012;Fenner et al, 2004;Ward et al, 2009) and forest ecosystems Hogberg et al, 2008;Subke et al, 2009).…”
Section: Introductionmentioning
confidence: 99%